Factors that control the spatial and temporal distributions of phosphorus, nitrogen, and carbon in the sediments of a tropical reservoir - Cardoso-Silva, Sheila [UNESP]; Ferreira, Paulo Alves de Lima; Figueira, Rubens César Lopes; da Silva, Daniel Clemente Vieira Rêgo; Moschini-Carlos, Viviane [UNESP]; Pompêo, Marcelo L. M. (Springer Nature, 2018)
The impacts of anthropic activities have had profound effects on the nitrogen (N) and phosphorus (P) cycles in many aquatic ecosystems. We investigated the spatial and temporal distributions of carbon (C), N, and P in the sediments of a tropical Paiva Castro Reservoir (São Paulo, Brazil), as well as their release and retention in the system. In 2010, surface sediments were collected at nine sites in the reservoir, and a core was obtained in the limnetic zone, in 2010. The core was dated using the 210Pb technique. The organic C content was estimated from organic matter concentration, which was measured by the loss-on-ignition method, and the concentrations of P and N were determined by spectrophotometry. Marked spatial heterogeneity in the Paiva Castro sediments associated with both natural variations in the water body and variations induced by human impacts was observed. Heterogeneity was evidenced by a decrease in the allochthonous contribution of organic matter (C/N) in the upstream-downstream direction and increases of N and P, mainly associated with water flows in the different compartments of the reservoir. In the core, C and N concentrations display significant positive correlations with increases in population and agricultural activities in the drainage basin through time. The C/P molar ratios in surface sediments are indicative of human impacts in the region, as C:P ratios in the sediment are low (7.8:1) compared to the Redfield ratio (C:P = 108:1). Predominance of oxic conditions at the sediment surface and particles sizes < 63 μm provided favorable conditions for P retention in the sediments, which helps prevent eutrophication. Approaches used in this research should be extended to other locations, especially in mesotrophic and oligotrophic reservoirs, to provide information on historical impacts in such aquatic ecosystems.
Keywords: Anthropic impacts; Eutrophication; Nitrogen; Paleolimnology; Phosphorus; Reservoir; Sediment core